Model Integrasi Konsep Green Building dalam Sistem Pemeliharaan Berkelanjutan untuk Meningkatkan Nilai Life Cycle Rumah Tinggal Sederhana - Wisdianti, Dara; Fitri, Rahmadhani (PT. Arsil Reka Engineering, 2026)
This research aims to develop a model that integrates green building concepts into a sustainable maintenance system, ultimately enhancing the life cycle value of Modest Houses (RTS) in Indonesia. The rationale for this study stems from the building sector's high energy consumption and emissions, coupled with current maintenance practices for modest houses that remain conventional, reactive, and focused on initial costs—thereby neglecting long-term efficiency. Utilizing a Research and Development (R&D) mixed-methods approach, this study maps the gap between GBCI GREEN HOMES principles and existing maintenance practices. It identifies relevant green building criteria during the operation and maintenance phases to design a practical and applicable maintenance model. The proposed model is tested and validated on selected RTS units through observations, interviews, and simple simulations to evaluate its economic and environmental impacts, as well as its effect on occupant comfort. The output of this research is a sustainable maintenance guideline designed to reduce operational costs, minimize environmental impacts, and extend the lifespan of modest houses. Simultaneously, it supports the broader sustainable development agenda and the transition toward healthier, more energy-efficient residential buildings.